Artificial Intelligence Driven Smart Office: Enhancing Employee Efficiency and Productivity in the Age of Machine Autonomy - Fazril Muhamad Mursyidhan; Yathaqi Witsqa, Rakha (International Journal Administration, Business & Organization, 2026)
Digital transformation is accelerating the adoption of smart offices powered by Artificial Intelligence (AI) and the Internet of Things (IoT) to enhance operational efficiency and employee productivity. This study examines the level of AI adoption, patterns of use, and employee perceptions regarding comfort and the perceived importance of AI in supporting workplace performance. A descriptive approach was applied through a literature review and a 5 point Likert based questionnaire. Primary data were collected from 28 respondents using convenience sampling and analyzed descriptively with Microsoft Excel. The findings show that 46.4% of respondents work in offices without AI, 32.1% in offices that already implement AI, and 21.4% in offices with potential adoption. AI usage is mostly occasional (46.4%), while 21.4% report never using it. The mean scores for comfort working alongside AI and the perceived importance of AI are both 3.75 (on a 1-5 scale), indicating a generally positive attitude despite limited adoption. The study concludes that AI driven smart offices have the potential to improve efficiency and productivity, but further advancements in digital literacy, employee training, and infrastructure readiness are needed. Practical recommendations and avenues for future research are provided to encourage broader and more responsible adoption.